Effect of fluoxetine on organ dysfunction and mortality in severe sepsis - Islam Abdelaal Abdelmouty Taher; Farouk Kamal Eldin; M. A. Wareth Eissa; Lobna A. Saleh; Osama A. Mohammed; Ahmed S. Doghish; Amr Sobhy Abdel Kway (PLoS ONE, 2026)
Introduction Sepsis is a leading cause of morbidity and mortality in intensive care units, characterized by a dysregulated host response to infection. Recent evidence suggests fluoxetine, a selective serotonin reuptake inhibitor, may exert immunometabolic effects beneficial in sepsis. The aim of this study is to evaluate the effect of fluoxetine on vasopressor duration, organ dysfunction, inflammatory markers, and mortality in adult patients with severe sepsis. Materials and methods In this single-center, randomized, double-blind, placebo-controlled trial conducted at Ain Shams University Hospitals (December 2024–June 2025), 46 patients with severe sepsis were randomized 1:1 to receive either fluoxetine (40 mg/day) or placebo in addition to standard sepsis care. The primary outcome was vasopressor duration. Secondary outcomes included Sequential Organ Failure Assessment (SOFA) scores, inflammatory biomarkers (CRP, TNF-α, IL-1, procalcitonin), lactate levels, ICU length of stay, and 28-day mortality. Results Fluoxetine significantly reduced vasopressor duration (6.2 ± 0.4 vs. 7.9 ± 0.8 days; p < 0.001), ICU stay (15.9 ± 1.6 vs. 17.1 ± 1.1 days; p = 0.005), and inflammatory markers by day 7, including TNF-α, IL-1, CRP, and procalcitonin (all p < 0.05). SOFA and APACHE II scores were also lower in the fluoxetine group on days 7 and 10. No significant difference in 28-day mortality was observed (8.7% vs. 17.4%; p = 0.381). Conclusions Fluoxetine as adjunctive therapy in severe sepsis may reduce vasopressor dependence, attenuate inflammation, and shorten ICU stay without increasing adverse effects. Its mortality benefit remains uncertain and warrants further investigation.